(untitled) (Experimental biology, 2020)
Regulation of the expression of chloroplast genes mainly occurs at the post-transcriptional level, in which 5’-untranslated regions (5’UTR) of plastid mRNA play a significant role. In transplastomic tobacco plants, we studied the effect of the 5’UTRs of the genomic RNA of potato Y-virus (5’PVY), as well as the 5’UTR of the plastid psbA gene (5’psbA) on the expression of the bacterial reporter uidA gene encoding β-glucuronidase (GUS). Genetic constructs containing the uidA gene were created under the control of identical transcriptional regulatory elements: the promoter and terminator of the psbA gene and two different 5’UTRs — 5’psbA and 5’PVY. Тobacco chloroplasts were transformed with these constructs by bioballistic method. Transplastomic lines showed approximately 24-fold differences in GUS activity. Replacing the natural 5’psbA with the heterologous 5’PVY resulted in a significant decrease in the synthesis of GUS protein. Key words: chloroplasts, protein synthesis, 5’UTR, transplastomic plants, reporter protein.